How should public health professionals engage with lay epidemiology?. Issue 8 (28th July 2006) - Allmark, P; Tod, A
Abstract : "Lay epidemiology" is a term used to describe the processes through which health risks are understood and interpreted by laypeople. It is seen as a barrier to public health when the public disbelieves or fails to act on public health messages. Two elements to lay epidemiology are proposed: (a) empirical beliefs about the nature of illness and (b) values about the place of health and risks to health in a good life. Both elements have to be dealt with by effective public health schemes or programmes, which would attempt to change the public's empirical beliefs and values. This is of concern, particularly in a context in which the lay voice is increasingly respected. Empirically, the scientific voice of standard epidemiology should be deferred to by the lay voice, provided a clear distinction exists between the measurement of risk, which is empirical, and its weighting, which is based on values. Turning to engagement with values, health is viewed to be an important value and is discussed and reflected on by most people. Public health professionals are therefore entitled and advised to participate in that process. This view is defended against some potential criticisms.